1996
DOI: 10.1002/(sici)1096-8628(19960503)63:1<203::aid-ajmg36>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of free neuraminic acid storage disease in childhood: Clinical, morphological and biochemical observations in three non-Finnish patients

Abstract: N‐acetylneuraminic acid (sialic acid) storage disease is a rare autosomal recessive lysosomal disorder: Clinically two major forms exist, an infantile type with severe progression leading to early death, and a milder form (Salla disease) with a protracted course. Intermediate forms may also exist. Diagnosis rests on the determination of an excessive excretion of sialic acid in urine and concomitant storage in fibroblasts, the severe forms exhibiting the highest excretion and storage. We present clinical, morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…6 Clinical data In contrast to our series (table 2), all the cases in the literature were diagnosed after birth, although the presence of antenatal signs was documented in 11 cases. [7][8][9][10][11][12][13][14][15][16] The earliest ultrasonographic sign was increased nuchal thickness at 10 GA preceding a more complete picture (case 11). The most prominent sign consisted of ascites discovered between 13 11 and 32 GA, 13 which could require repeated punctures in utero (our case 8 and case 2 of Lemyre et al 12 ) or at birth (case 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Clinical data In contrast to our series (table 2), all the cases in the literature were diagnosed after birth, although the presence of antenatal signs was documented in 11 cases. [7][8][9][10][11][12][13][14][15][16] The earliest ultrasonographic sign was increased nuchal thickness at 10 GA preceding a more complete picture (case 11). The most prominent sign consisted of ascites discovered between 13 11 and 32 GA, 13 which could require repeated punctures in utero (our case 8 and case 2 of Lemyre et al 12 ) or at birth (case 4).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] The earliest ultrasonographic sign was increased nuchal thickness at 10 GA preceding a more complete picture (case 11). The most prominent sign consisted of ascites discovered between 13 11 and 32 GA, 13 which could require repeated punctures in utero (our case 8 and case 2 of Lemyre et al 12 ) or at birth (case 4). Antenatal ascites was absent in two of our four neonatal cases (although it was present at birth in case 2), in two further affected fetuses in families 2 and 7 at 12-13 GA, and in one case in the literature, 14 and was only transient in case 3 of Lemyre et al 12 In some cases, complete fetal hydrops was described, although it was never as severe as in our 21 cases of antenatal mucopolysaccharidosis VII (personal unpublished data) and never led to severe pulmonary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Salla's disease is a defective lysosomal membrane transport system for SA, in which the level of free SA in urine is about 5-to 10-fold compared with normal [42]. Sewell et al [43] have showed an increased urinary excretion of free SA and confirmed this in cultivated fibroblasts. In sialuria, a rare defect with excessive synthesis of SA, free ᮊ 1999 Blackwell Science Ltd, European Journal of Clinical Investigation, 29, 413-425 Table 2 Mean Ϯ SD, serum total SA (TSA), lipid-bound SA (LSA), TSA/total protein (TP) and protein-bound SA (PBSA) levels in healthy humans SA levels can be elevated 70-to 200-fold [44,45].…”
Section: Urinementioning
confidence: 98%
“…In these, SA accumulates in lysosomes, because of lysosome membrane not transporting SA. Although Salla's disease presents with neurological complications, but only slightly shortened lifespan, victims of infantile SA storage disorder possess a mean lifespan of 19 months, demonstrating a wide variety of symptoms [43,109]. In a rare condition of sialuria, excessive amounts of free SA is excreted in urine.…”
Section: Inherited Disorders Of Samentioning
confidence: 99%
“…On the other hand, measuring SA in urine is an established method for diagnosing inherited SA storage diseases such as Salla disease, sialuria, and sialidosis (Aula et al, 1979;Mancini et al, 1991;Krasnewich et al, 1993;Berra et al, 1995;Sewell et al, 1996). It is unclear why high alcohol consumption does not affect the urine levels of SA, whereas it affects the serum and saliva concentrations.…”
Section: Discussionmentioning
confidence: 99%